2017
DOI: 10.1093/ofid/ofx177
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Antiretroviral Treatment and Avascular Bone Necrosis: The Swiss HIV Cohort Study

Abstract: BackgroundHIV-infected individuals have an increased risk of avascular bone necrosis (AVN). Antiretroviral therapy (ART) and particularly protease inhibitors (PI) have been implicated as a risk factor. We aimed to study the associations of ART with the occurrence of AVN among Swiss HIV Cohort Study participants (SHCS).MethodsWe used incidence density sampling to perform a case control study within the Swiss HIV Cohort Study (SHCS) comparing prospectively collected AVN cases and controls by conditional logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…30 Ritonavir has been found to displace drugs metabolised by CYP3A, leading to increased bioavailability and potentiation of the adverse effect of systemically available corticosteroids. 5,30 Although it is important to note that ritonavir use alone has been associated with avascular necrosis of bone, 31 patients demonstrating multiple features of hypercortisolism, as observed in this patient with Cushing's syndrome and avascular necrosis of the shoulder while on ritonavir and a corticosteroid, should prompt consideration for an interaction between the medications.…”
Section: Discussionmentioning
confidence: 86%
“…30 Ritonavir has been found to displace drugs metabolised by CYP3A, leading to increased bioavailability and potentiation of the adverse effect of systemically available corticosteroids. 5,30 Although it is important to note that ritonavir use alone has been associated with avascular necrosis of bone, 31 patients demonstrating multiple features of hypercortisolism, as observed in this patient with Cushing's syndrome and avascular necrosis of the shoulder while on ritonavir and a corticosteroid, should prompt consideration for an interaction between the medications.…”
Section: Discussionmentioning
confidence: 86%
“… 40 One recent study revealed a strong association between high-activity antiretroviral therapy and development of osteonecrosis, although the authors caution that the association does not imply a pathologic role. 40 Other studies have found no association between osteonecrosis and antiretroviral therapy (ART), citing instead association with alcohol, hyperlipidemia, 41 or low nadir CD4 counts, 42 although the mechanism is not well understood.…”
Section: Pathophysiology and Pathogenesismentioning
confidence: 99%
“…AVN may be caused by trauma, such as fracture, particularly displaced fractures [ 18 ], or it can be non-traumatic. The pathogenesis of non-traumatic osteonecrosis is unclear, but there are several established risk factors such as corticosteroid treatment, alcohol abuse, rheumatic diseases, bone-marrow transplantation, or antiretroviral treatment [ 15 , 19 , 20 , 21 , 22 , 23 ]. Diabetes mellitus (DM), which causes disease of both large vessels (macroangiopathy) and small vessels (microangiopathy) [ 24 ], can also increase the risk of avascular osteonecrosis [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%